Supply Chain Efficiency Analysis of Rice Commodities in Improving Farmers' Profit Margins in Indramayu Regency - Ikhsan Nendi; Chiska Nova Harsela; Feri Hardiyanto; Siti Komara; Anisa Ayu Dwi Lestari (PT Mattawang Mediatama Solution, 2026)
This study investigates the supply chain efficiency of rice commodities in Indramayu Regency and its implications for improving farmers' profit margins. Indramayu Regency is one of Indonesia's principal rice-producing regions, yet farmers continue to receive disproportionately low returns due to inefficiencies across the supply chain, including excessive intermediary layers, high post-harvest losses, and weak market integration. This study employs a quantitative approach using survey data from 120 rice farmers and 45 supply chain actors selected through stratified random sampling. Data were collected between January and June 2024. Analytical methods include marketing margin analysis, farmer's share analysis, Supply Chain Operations Reference (SCOR) efficiency scoring, and multiple regression to identify determinants of profit margin. The results show that farmers retain only 42.6% of the final consumer price (Channel III), compared to 68.4% in the shortest marketing channel (Channel I). Supply chain efficiency scores averaged 0.73 across all actors, with rice millers recording the highest efficiency (0.87) and farmers the lowest (0.61). Regression analysis confirms that channel choice, access to milling technology, and cooperative membership significantly improve profit margins. The findings suggest that policy interventions focused on reducing intermediary dependency, strengthening farmer cooperatives, and investing in post-harvest infrastructure can substantially increase rice farmers' income in Indramayu Regency.